CO-CREATION IN TEACHING ENGLISH TO TERTIARY STUDENTS - Sahyoni Sahyoni; Lia Agustina Damanik; Hanifah Oktarina (Prominent, 2024)
Innovative teaching approaches that encourage active learning are becoming more and more popular in the ever-changing educational landscape. One such paradigm that has attracted a lot of interest is co-creation, an educational strategy that stresses student engagement and collaborative learning. This study aims to investigate the implementation of co-creation in teaching Basic Grammar, Basic Writing and Translation. Then, this research also aims to analyze the effect of the implementation of co-creation in the classroom. The study utilizes qualitative research methodology and was conducted at STAIN Mandailing Natal, focusing on students enrolled in the English Language Education Program. Data was collected through focus group discussions, observations, and interviews. The findings highlight various co-creation techniques used, such as peer feedback, collaborative projects, and grammar prompts, which have resulted in positive outcomes for students, including increased engagement, collaboration, autonomous learning, and critical thinking skills. Overall, the incorporation of co-creation in the classroom has enhanced the academic experience for students in the English Language Education Program. Further exploration is recommended to understand its full potential and applicability across different educational settings and subjects. Besides, future researchers could focus on quantifying the effects of co-creation on student outcomes and delve into potential challenges and solutions in its implementation.